Oral infectivity through carnivorism in murine model of Trypanosoma cruzi infection - Torres, Víctor; Contreras, Víctor; Gutiérrez, Bessy; San Francisco, Juan; Catalán, Alejandro; Vega, José Luis; Moon, Kyung-Mee; Foster, Leonard J.; de Almeida, Rafael F.; Kalergis, Alexis M.; González, Jorge (Frontiers in Cellular and Infection Microbiology, 2024)
T. cruzi oral transmission is the most frequent transmission mechanism in wild animals. This observation led to the hypothesis that consuming raw or undercooked meat from T. cruzi infected animals may be responsible for transmitting the infection. Therefore, the objective of this study was to investigate host-pathogen interactions between the parasite and gastric mucosa and the role of meat consumption from infected animals in the T.cruzi oral transmission. Infectivity assays were performed on AGS cells in the presence or absence of mucin, and the roles of pepsin and acidic pH were determined. Moreover, mice were fed with muscle tissue obtained from mice in the acute phase of infection by the clone H510 C8C3hvir of T. cruzi, and the infection of the fed mice was monitored . Similarly, we assessed the infective capacity of T. cruzi trypomastigotes and amastigotes by infecting Balb/c mice. Adhesion assays of T. cruzi proteins to AGS stomach cells were performed, and the adhered proteins were detected by western blotting, LC-MS/MS and bioinformatics analysis. Trypomastigote migration in the presence of mucin was reduced by approximately 30%, whereas in the presence of mucin and pepsin at pH 3.5, only a small proportion of parasites were able to migrate (∼6%). Similarly, the ability of TCTs to infect AGS cells in the presence of mucin is reduced by approximately 20%. In all cases, 60-100% of the animals were fed meat from mice infected in the acute phase or infected with trypomastigotes or amastigotes developed high parasitemia, and 80% died. The adhesion assay showed that cruzipain is a molecule of trypomastigotes and amastigotes that binds to AGS cells. LC-MS/MS and bioinformatics analysis, also confirmed that tran-sialidase, cysteine proteinases, and gp63 may be involved in TCTs attachment or invasion because they can potentially interact with different proteins in the human stomach mucosa. In addition, several human gastric mucins have cysteine protease cleavage sites. Then, consuming meat from infected animals in the acute phase allows the T. cruzi infection. Similarly, trypomastigotes and amastigotes could infect mice when administered orally, whereas cysteinyl proteinases and transialidases appear to be relevant molecules in this infective process.